Development and grain yield of common bean cultivars according to sowing season - Catuchi, Tiago Aranda; Guidorizzi, Fernando Vieira Costa [UNESP]; Peres, Vinicius José Souza; Dias, Eduardo Silva; Parmezan, Gabriel Chaves; Galdi, Leonardo Vesco (UNESP - Universidade Estadual Paulista, 2019)
The cycle and grain yield of bean crops can be influenced by several factors, among them sowing season and bean cultivar. The objective of this work is to evaluate the development, production components, and grain yield of common bean cultivars in function of sowing seasons. The experiment was conducted at the Experimental Farm of Universidade do Oeste Paulista in the municipality of Presidente Bernardes, São Paulo state, in 2016. The experimental design was randomized blocks in a 4 x 4 factorial design with four replications. The treatments were four sowing seasons (SS1 - April 12; SS2 - May 14; SS3 - June 11; and SS4 - July 14), and four common bean cultivars (BRS Estilo, BRS Pérola, BRS Requinte, and IPR Campos Gerais). The phenological stages V4, R6 and R9, plant height, plant population, number of pods per plant, mass of 100 grains, and grain yield were influenced by sowing seasons and bean cultivars. The highest grain yields for the cv. BRS Estilo, BRS Requinte and IPR Campos Gerais were obtained at SS2. However, for the cv. BRS Pérola, it occurred at SS4. At SS1, the highest grain yield was obtained by the cv. BRS Estilo, and other sowing seasons by the cv. BRS Pérola.
Keywords: Cultivars; Grain yield; Phaseolus vulgaris; Sowing seasons